Efisiensi Saluran Distribusi Area Pemasaran PT Nutrifood Indonesia di Pulau Jawa Menggunakan Data Envelopment Analysis - Aditia Sovia Pramudita (Coopetition : Jurnal Ilmiah Manajemen, 2020)
Competition in the growing world of commerce has an impact on strategy for a company. Every company wants an increase in sales and revenue along with meeting customer needs. Distribution system as one of the elements in the marketing mix has an important role in fulfilling customer needs. Selecting the right distribution channel in marketing products can be an alternative to fulfill customer needs efficiently. PT Nutrifood Indonesia as an FMCG company needs a fast product distribution cycle because of this the process must be carried out efficiently. This study uses the DEA method in calculating the relative efficiency value of each DMU by using each of its inputs and outputs. The study was conducted in 13 marketing distribution areas of Java, which are Bandung, Banjar, Banyuwangi, Bekasi, Bogor, Bojonegoro, Jakarta, Karawang, Majalengka, Semarang, Tangerang, Tegal and Yogyakarta. The results showed that there were 8 out of 13 areas of product marketing distribution that were technically inefficient based on the results of the DEA calculation of the BCC model with the assumption of VRS output orientation. The improvement target is carried out in the inefficient DMU in order to increase its efficiency value by reducing the input variable and increasing the output variable.